Inequality in the Local Public Sector - Bucovetsky, Sam (Journal of Political Economy, 1982)
Effects on renters' welfare of changes in local government spending are examined in a multijurisdiction model. In equilibrium each income class chooses the jurisdiction whose combination of local public output and housing price maximizes utility. Comparative-static analysis of this equilibrium is used to show how inequality in local public expenditure benefits low-income residents. If low-income residents are observed to choose jurisdictions with low levels of per capita public expenditure, then they may be worse off by outside aid which increases local public expenditure in their jurisdictions. The advantages of inequality in the local public sector also exist when a program of tax base equalization is introduced.